2021
DOI: 10.3390/pharmaceutics13122147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Size on Magnetic Polyelectrolyte Microcapsules Behavior: Biodistribution, Circulation Time, Interactions with Blood Cells and Immune System

Abstract: Drug carriers based on polyelectrolyte microcapsules remotely controlled with an external magnetic field are a promising drug delivery system. However, the influence of capsule parameters on microcapsules’ behavior in vivo is still ambiguous and requires additional study. Here, we discuss how the processes occurring in the blood flow influence the circulation time of magnetic polyelectrolyte microcapsules in mouse blood after injection into the blood circulatory system and their interaction with different bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…Also, magnetically sensitive objects have been considered a highly effective tool in solving such a challenging task as reducing side effects from drug applications drawing on the example of polyelectrolyte microcapsules. Over the past decades, a vast amount of studies have shown the high potential of polyelectrolyte magnetic microcapsules' application as containers for remotely controlled drug delivery [8,[10][11][12][13]. This concept is based on the idea of the systemic administration of magnetically sensitive drug-loaded micro-containers and their targeting of the affected area using an external magnetic field source [14].…”
Section: Introductionmentioning
confidence: 99%
“…Also, magnetically sensitive objects have been considered a highly effective tool in solving such a challenging task as reducing side effects from drug applications drawing on the example of polyelectrolyte microcapsules. Over the past decades, a vast amount of studies have shown the high potential of polyelectrolyte magnetic microcapsules' application as containers for remotely controlled drug delivery [8,[10][11][12][13]. This concept is based on the idea of the systemic administration of magnetically sensitive drug-loaded micro-containers and their targeting of the affected area using an external magnetic field source [14].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors affect the behavior of carriers in the body. Multiple studies have shown that the nature, size, surface potential, and other characteristics of vehicles fundamentally affect their biodistribution, cell interaction, circulation time, and hydrodynamics in the blood flow [ 13 , 14 , 15 , 16 ]. Often, carriers’ features providing the effective administration procedure, such as prolonged circulation in the blood flow and low immunogenicity, impede the other desirable features of the DDS, such as a high internalization efficiency by cancer cells and drug release.…”
Section: Introductionmentioning
confidence: 99%
“…In these regards, incorporating magnetic nanoparticles into MOFs with the potential for use in magnetic-based diagnostic approaches and as an effective technique for carrying drugs directly to a specific site through external magnetic fields has attracted much attention. This desired targeting behavior limits drug spreading in the general circulation and reduces side effects. Moreover, superparamagnetic nanoparticles can reduce the spin–spin T 2 *-relaxation time during magnetic resonance imaging (MRI), enhancing contrast in T 2 -weighted images using magnetic nanoparticles. , Furthermore, magnetic fields as external stimuli can also induce the release of drugs from magnetic nanocarriers. , Numerous reports are available on magnetic drug delivery systems; however, most of them suffer from several limitations such as low stability, swelling, and insignificant controllability. Therefore, the design and construction of materials with a magnetic core as a drug delivery system that can overcome the disadvantages mentioned above would be valuable. A MOF-based magnetic nanocomposite was prepared by the incorporation of Fe 3 O 4 nanorods in Cu 3 (BTC) 2 nanocrystals (BTC; benzene-1,3,5-tricarboxylate).…”
Section: Introductionmentioning
confidence: 99%